Pengaruh Pengangguran dan Distribusi Zakat terhadap Kemiskinan di Indonesia - Jumhur; Sukmawati, U. Sulia; Ittasyaq, Nurul Laili (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This research is motivated by the high poverty rate in Indonesia and the ongoing theoretical debate regarding its influencing factors, specifically unemployment and Islamic philanthropic instruments such as zakat. This study aims to analyze the relationship between the open unemployment rate and zakat distribution on poverty levels across 38 provinces in Indonesia during the 2020-2024 period. The research method employed is quantitative with panel data, combining time-series and cross-sectional data. The data are sourced from official publications of the Indonesian Central Bureau of Statistics (BPS) and BAZNAS RI, subsequently analyzed using correlation tests to identify the direction and strength of the relationships between variables. Theoretically, the results indicate that unemployment is positively related to poverty due to the loss of income sources, while zakat plays a significant role as a wealth redistribution instrument that is negatively related to poverty levels. Empirically, unemployment dynamics in Indonesia experienced a significant increase in 2021 due to the COVID-19 pandemic before showing a declining trend until 2024, directly impacting the fluctuations in poverty rates across various regions.